2021
DOI: 10.1016/j.heliyon.2021.e07262
|View full text |Cite
|
Sign up to set email alerts
|

Nutraceutical regulation of miRNAs involved in neurodegenerative diseases and brain cancers

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 236 publications
(311 reference statements)
0
5
0
Order By: Relevance
“…MiRNAs have been proposed as potential biomarkers for disease ( Ghosh et al, 2021 ). Currently, CTE can only be diagnosed at autopsy and ALS is typically diagnosed after motor functions have declined.…”
Section: Discussionmentioning
confidence: 99%
“…MiRNAs have been proposed as potential biomarkers for disease ( Ghosh et al, 2021 ). Currently, CTE can only be diagnosed at autopsy and ALS is typically diagnosed after motor functions have declined.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that nutritional components and nutraceuticals can control the activity of miRNAs that have a role in age-related disorders. This suggests that they could be used as potential treatments ( Ghosh et al, 2021 ).…”
Section: Implications For Prevention and Treatment Of Age-related Dis...mentioning
confidence: 99%
“…The gene expression patterns linked to aging and age-related disorders can be influenced by foods such as macronutrients, micronutrients, and trace minerals, which in turn can change miRNA profiles ( Beckett et al, 2014 ; Quintanilha et al, 2017b ). In addition, nutraceuticals have demonstrated potential as treatment methods for age-related diseases by altering miRNA expression ( Alnuqaydan, 2020 ; Ghosh et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Brain tumours typically have a poor prognosis with an average life expectancy of approximately one year [75,76]. Among brain cancer types, glioblastoma multiforme is a common tumour [77], with a mean survival rate of ~ 3.3% at three years post-diagnosis [77,78]. Brain cancers have traditionally been treated with a surgical procedure followed by systemic chemotherapy, but these are limited due to the effects on the brain and severe toxicity.…”
Section: Brain Cancermentioning
confidence: 99%